Conservation and restoration of birch-bark box discovered from Xiongnu tomb - Narmandakh, Nandintsetseg (Studia Archaeologica, 2023)
In 2022, The conservation and restoration work was carried out in order to extend to stretch the bent and deformed birch bark box, to preserve it in its original form, to detail the scribbled pictures decorated with rare and unusual images, and to determine the ethnographic artifacts of the Xiongnu period. As a result of the research, it is important to publicize and spread the traditions of ancient nomadic household culture as a museum exhibit. Our research materials were discovered as a result of the excavation of the 6th Xiongnu Tomb (Ex.10.21) in the Zuun hotgor of Shiriin Chuluu, Altanshiree Sum, Dornogobi Province, within the framework of the joint Mongolian-American project “Archaeological Research of the Gobi Region”. The present study aims to appropriate methods of restoration were developed, the design, structure, and characteristics of the materials were determined, and the bent part was stretched to its original appearance. The completed birch bark box was strengthened with trehalose sugar (C12H22O11) and the bronze mirror fragments were strengthened with the benzotriazole (C6H5N3) method, and preservation and conservation activities were carried out in accordance with the appropriate procedures. Now, this artifact is 5.5 x 10 cm in size and weighs 30 g. It turned out that the shape of the box was drawn surrounded by sharp objects on the outside to represent the shape of the Ger. Үйсэн эдлэлийн хадгалалт хамгаалалт, туршлага /Хүннүгийн булшнаас илэрсэн үйсэн савны жишээгээр/ Товчлол. Тус өгүүлэлд Дорноговь аймгийн Алтанширээ сумын Ширийн чулууны Зүүн хотгор дэрсний 6-р хүннү булшны /Ех.10.21/ малтлага судалгааны ажлын үр дүнд илэрсэн үйсэн савыг сэргээн засварласан арга, туршлагын талаар өгүүлж байна. Үйсэн сав нь нэг талаараа шахагдаж нугалран анхны хэлбэрээ алдсан, их биеийн хэсэг нэлэнхийдээ судал, хана хэсгийн нугалаасаар хагарч цуурсан байх ба голоороо болон оёдлын залгаа хэсгээрээ 3 хэсэг болж хуваагдсан гэмтэлтэй, хөрс шорооны гүн бохирдолтой, хадгалалтын нөхцөл дунд байв. Уг олдворын хэлбэр, бүтэц, анхны төрхийг тодорхойлохын тулд нугаларсан хэсгийг Трехалос уусмалаар чийглэн зөөлрүүлэн тэнийлгэж соёлын өвийн хадгалалт хамгаалалт, сэргээн засварлалтын журмын дагуу олдворын шинжилгээ, цэвэрлэгээ, нөхөх, наах бэхжүүлэх зэрэг үе шатыг бүрэн хэрэгжүүлж ажиллалаа. Соёлын өвийн хадгалалт хамгаалалт, сэргээн засварлалтын ажлын үр дүнд үйсэн савны өндөр 5.4 см, зузаан 0.4 см, амсрын голч 10.2 см, ёроол хэсгээрээ 10.7 см хэмжээтэй, жин 30 гр. Мөн гадна талаараа тойруулан нарийн үзүүртэй зүйлээр гэрийн хэлбэрийг сараачмал зураасаар дүрсэлсэн болох нь тодорхой харагдаж байна. Түлхүүр үг. Хүннүгийн үе, үйсэн сав, хадгалалт хамгаалалт